Implementation of Hardening for Optimization of Wireless Local Area Network Security - Rahmat Novrianda Dasmen; Muhammad Reihan Pratama (LPPM Universitas Islam 45 Bekasi, 2025)
Computer networks use two main methods for data transmission, namely wired and wireless networks or what is known as a Wireless Local Area Network (WLAN). In WLAN networks, the security standard usually used is the WiFi Protected Access 2 Pre-Shared Key or WPA2-PSK protocol, which utilizes SSID and password. Despite using security mechanisms such as WPA2-PSK, criminal activities such as intrusion into the network still occur. Therefore, it is necessary to improve the network security system to ensure that the WLAN network is more secure and can minimize potential risks to users. This study aims to improve and optimize the WLAN network security system through vulnerability scanning using the Nessus tool to test the level of security on the WLAN network and the application of hardening methods to strengthen and disguise vulnerabilities on the WLAN network, which includes various security techniques such as applying raw firewalls and firewall filters, limiting ports and services used and disabling services that are not needed to minimize vulnerabilities, disabling the Mikrotik neighbor discovery protocol service on the router, and implementing port knocking as an additional layer of security. The results of the study show that applying vulnerability scanning techniques and hardening methods can help minimize the level of risk of vulnerabilities found and make the resilience of the WLAN network more optimal so as to avoid potential intrusions and threats of attacks.